Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Ibu Nifas tentang Hiperbilirubinemia - Yuhemy Zurizah; Intan Sari (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2024)
Hyperbilirubinemia is a common issue experienced by newborns. In the bodies of newborns, the organs have not yet developed fully, leading to an increase in bilirubin production. Their ability to filter bilirubin is not well established, and bilirubin transport can be disrupted in infants. Sometimes, the liver cannot process bilirubin effectively, resulting in an excess of bilirubin in the body; this condition is referred to as hyperbilirubinemia. Although hyperbilirubinemia occurs frequently, if not managed properly, it can lead to complications, including irreversible brain damage.The research design employed in this study was a pre-experimental design, which involved a one-group pre-test and post-test method conducted at Budi Mulia Medika Clinic in Palembang from September to October 2024. The sample consisted of 35 postpartum mothers selected through non-probability accidental sampling. Data collection was carried out via questionnaires, and statistical analysis included paired t-tests to assess the differences in knowledge levels before and after health education. The results indicated a significant increase in knowledge, with pre-test mean scores of 11.31 (SD = 2.610) rising to post-test mean scores of 15.91 (SD = 3.551), yielding a p-value of 0.000. The conclusions of this study emphasize the need for structured health education programs to enhance mothers' understanding of hyperbilirubinemia, which could ultimately lead to improved health outcomes for newborns. The findings highlight the role of healthcare providers in delivering essential health education to reduce the incidence and complications of hyperbilirubinemia among neonates.